Chromosome counting in the mouse zygote using low‐invasive super‐resolution live‐cell imaging. (12th February 2022) - Hatano, Yu; Mashiko, Daisuke; Tokoro, Mikiko; Yao, Tatsuma; Yamagata, Kazuo
Abstract: In preimplantation embryos, an abnormal chromosome number causes developmental failure and a reduction in the pregnancy rate. Conventional chromosome testing methods requiring biopsy reduce the risk of associated genetic diseases; nevertheless, the reduction in cell number also reduces the pregnancy rate. Therefore, we attempted to count the chromosomes in mouse embryos using super‐resolution live‐cell imaging as a new method of chromosome counting that does not reduce the cell number or viability. We counted the 40 chromosomes at the first mitosis by injecting embryos with histone H2B‐mCherry mRNA under conditions by which pups could be obtained; however, the results were often an underestimation of chromosome number and varied by embryo and time point. Therefore, we developed a method to count the chromosomes via CRISPR/dCas‐mediated live‐cell fluorescence in situ hybridization targeting the sequence of the centromere region, enabling us to count the chromosomes more accurately in mouse embryos. The methodology presented here may provide useful information for assisted reproductive technologies, such as those used in livestock animals/humans, as a technique for assessing the chromosomal integrity of embryos prior to transfer. Abstract : Low‐toxic super‐resolution observation enables chromosome counting in preimplantation embryos without cell collection.